Pengaruh Digital Marketing dan Harga Terhadap Minat Beli Konsumen Pengguna Shopee di Bandar Lampung dalam Perspektif Bisnis Islam: Studi pada Gen-Z Pengguna Shopee di Bandar Lampung - Rizky Ananda Faisal; Evi Ekawati; Yulistia Devi (JURNAL RISET MANAJEMEN (JURMA), 2024)
The pre-survey findings show how information can influence interest in purchasing, whether it is information about products marketed on digital platforms or information about the price of a product listed. This is a very interesting issue to be discussed further. This research aims to find out whether digital marketing has a significant effect on buying interest. To find out whether price has a significant effect on buying interest. To find out whether digital marketing and price have a significant effect on buying interest. To explain digital marketing and prices from an Islamic business perspective. This research method is a descriptive method with a quantitative approach. The sampling technique in this research used probability sampling with a purposive sampling method; a total sample of 100 Gen-Z Shopee users in Bandar Lampung were used as respondents. The data analysis techniques used in this research are multiple linear regression techniques, coefficient of determination techniques, partial hypothesis testing (T-test), and simultaneously (F test). The results of this research using partial hypothesis testing (T-test) show that digital marketing has a significant effect on purchase interest. Price does not have a significant effect on purchase intention. From the simultaneous hypothesis test (F-test), it can be seen that digital marketing and price have a significant effect on buying interest. In Islamic business, digital marketing and pricing must be based on honesty, transparency, and fairness.